Applications of laser scanning to structures in laboratory tests and field surveys. Issue 1 (14th March 2013) - Mosalam, Khalid M.; Takhirov, Shakhzod M.; Park, Sangjoon
SUMMARY The capabilities and advantages of laser scanners used for structural engineering applications to assess structural damage in laboratory tests and post‐earthquake field survey are discussed. High definition laser scans have many advantages over conventional instrumentation in laboratory setting: (i) capture three dimensional global deformations of large objects with accuracy; (ii) enable graphical post‐processing based on a location of the acquired points in space and utilizing the light intensity red–green–blue (RGB) values of scanned images; (iii) access to objects without spatial constraint and remote monitoring by scanning from a distance; and (iv) reduce workload for installing instruments. Therefore, high definition laser scans have been successfully used in laboratory tests, and several case studies are presented to demonstrate the accuracy of laser scanner measurements. In addition, this paper makes the first attempt to demonstrate the use of high‐definition laser scanning technology in field surveys of structures damaged during January 2010 Haiti earthquake. Damage assessments were performed for several structures using the scans, and the results were compared with qualitative results of visual ground survey. The techniques of gathering and disseminating critical information employed herein is expected to have major impact on future structural laboratory tests and field investigations. Copyright © 2013 John Wiley & Sons, Ltd.